DYSTOCIA IN CATTLE DUE TO FETAL HYDROCEPHALUS - MURALI, REVATHY M; VEERABRAMHAIAH, K; PRAVEEN, SUNNY; BABU, ANILA; VARDHAN M, SANTHA (The Indian Journal of Animal Reproduction, 2022)
A case of dystocia in non-descript cow due to hydrocephalus fetus was reported. Dead fetus was delivered bycaesarean section using local and high caudal epidural anaesthesia by adopting the standard operating procedure.
Keywords: Cow; Non Descript; Dystocia; Fetal hydrocephalus; Caesarean section